Crosstalk Between Kappa Opioid and Dopamine Systems in Compulsive Behaviors - Escobar, Angélica del Pilar; Casanova, José Patricio; Andrés, María Estela; Fuentealba, José Antonio (Frontiers in Pharmacology, 2020)
The strength of goal-oriented behaviors is regulated by midbrain dopamine neurons. Dysfunctions of dopaminergic circuits are observed in drug addiction and obsessive-compulsive disorder. Compulsive behavior is a feature that both disorders share, which is associated to a heightened dopamine neurotransmission. The activity of midbrain dopamine neurons is principally regulated by the homeostatic action of dopamine through D2 receptors (D2R) that decrease the firing of neurons as well as dopamine synthesis and release. Dopamine transmission is also regulated by heterologous neurotransmitter systems such as the kappa opioid. Much of our current knowledge of the kappa opioid system and its influence on dopamine transmission comes from preclinical animal models of brain diseases. In 1988, using cerebral microdialysis, it was shown that the acute activation of the Kappa Opioid Receptors (KOR) decreases synaptic levels of dopamine in the striatum. This inhibitory effect of KOR opposes to the facilitating influence of drugs of abuse on dopamine release, leading to propose the use of KOR agonists as pharmacological therapy for compulsive drug intake. Surprisingly, 30 years after, KOR antagonists instead are currently proposed to treat drug addiction. What happened during these years to generate this drastic change of paradigm? The collected evidence suggests that the effect of KOR on synaptic dopamine levels depends on the frequency of KOR stimulus and the timing to other incoming stimuli to dopamine neurons, as well as sex and species differences. Conversely to its acute effect, chronic KOR activation seems to facilitate dopamine neurotransmission and dopamine-mediated behaviors. The opposing actions exerted by acute versus chronic KOR activation have been associated with an initial aversive and a delayed rewarding effect, during the exposure to drugs of abuse. Compulsive behaviors induced by repeated activation of D2R are also potentiated by the sustained co-activation of KOR, which correlates with decreased synaptic levels of dopamine and sensitized D2R. Thus, the time-dependent activation of KOR impacts directly on dopamine levels affecting the tuning of motivated behaviors. This review analyzes the contribution of the kappa opioid system to the dopaminergic correlates of compulsive behaviors.